Inequalities and territorial development: crisis and perspectives of the Cohesion Policy - Picascia, Concetta (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
The European Union is currently experiencing a legitimacy crisis due, among other things, to the poorly governed effects of globalization and financialization of the economy, and to populist and nationalist drifts that compromise the stability of the integration and peace project, built by our fathers. founders. Through an institutional reading of what can now be defined as the long path of the Cohesion Policy, we intend to highlight how the reference to supra-state regulatory mechanisms that favor strategies of integration and territorial rebalancing is necessary to relaunch the social pact between the community and the political authority, especially in a phase of serious economic and social crisis that we are experiencing due to the effects of the Covid-19 pandemic.